Letter : Spain. The Czecho Slovakian situation - McKenna, Tom
012a-0012-001 Mr Bolton The National Union of Blastfurnacemen, Ore Miners, Coke Workers and Kindred Trades. 93, Borough Road West, Middlesbrough Thomas McKenna, General Secretary. H.V.Tewson Esq., The Trades Union Congress General Council, Transport House. Smith Square, London W.C. 22nd November 1938 Dear Mr.Tewson, Spain The Czecho Slovakian Situation. In my letter to you of the 19th inst., I got mixed up in dates, and in the first paragraph, I should have said that the meeting at Zurich takes place on the 27th and 28th November, i.e., next Sunday and Monday. I also made another error in asking "what are and have been the activities of the Joint Industrial Council", which of course should have been the "National Council of Labour". I should be glad to ask a further favour from you and that is, to give me the latest information regarding our efforts for the Spanish people, and as to what steps are being taken by the National Council of Labour to prevent Chamberlain conceding belligerent rights to Franco. Hoping that you can oblige. Yours faithfully, Thomas McKenna INTERNATIONAL METALWORKERS FEDERATION 292/946/12a/12